PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN FLIPCHART TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI KEANEKARAGAMAN HAYATI - Nopiani Fransiska; Kurnia Ningsih; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
This study purpose to determine the effect of the SAVI (Somatic Auditory Visualization Intellectualy) learning model assisted by flipchart media on the learning outcomes of stundents in the concept of biodiversity concept in class X SMA PGRI 1 Pontianak. The from of research used was quasy experimental design with a nonequivalent control group design. The research sample consisted ot two classes, namely class xa as an experimental class and class xb as acontrol class, the technique used in sampling is technique. The instrument used was a multiple choice with 20 items. The average score of the experimental class learning outcomes 14,21 while the control class 12,83. U-Mann Whitney test result abtained that Zcount (-2,47) < -Ztable (-1,96) these result indicate there are differences in learning outcomes of students who are taught with the SAVI learning model assisted by flipchart media and who are taught using conventional models. Through the calculation of the effect size, the SAVI learning model assisted by flipchart media has an effect of 25,17% on the learning outcomes of grade X stundest of SMA PGRI 1 Pontianak.